Feminist Catholic Theological Ethics: Conversations in the World Church - Kalambukattu, Naiju Jose (Asian Horizons, 2019)
Linda Hogan & Agbonkhianmeghe E. Orobator, ed., Feminist Catholic Theological Ethics: Conversations in the World Church, Bengaluru: Dharmaram Publications, 2016, Pages: x+300. ISBN: 9789384964-60-3.